Dependency of Financial Information Disclosure Quality on Auditor Expertise, Tenure, and Size: Evidence from the Iraq Stock Exchange - Ali Mohaisen, Hussein; Saedi, Rahman; Sabah Ali, Khalid; Mohammadi Khoshouei4, Hamzeh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this research is to examine the impact of auditor expertise, tenure, and size on the quality of information in the context of the Iraq Stock Exchange. We aim to explore the extent to which the lack of quality in information reporting can adversely affect investors’ ability to make more precise and effective decisions, thereby increasing transaction costs. Methodology: From a target population of 127 financial companies active in the Iraq Stock Exchange between 2015 and 2023, we selected 46 companies using a systematic elimination method. By employing a descriptive correlational research design, we attempted to explain the relationship between the target variables under investigation and the quality and transparency of financial information disclosure. Findings: We found that auditor expertise, tenure, and size play a crucial role in ensuring the quality of financial information reporting. Conclusion: Our findings can have significant implications for investors, company managers, and auditing institutions. The results highlight the necessity of selecting auditing firms that utilize concise and practical planning schemes to ensure the quality of financial information reports of companies trading on the Iraq Stock Exchange (ISX).